2013
DOI: 10.4028/www.scientific.net/amm.320.495
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Research of the Sustained Release Drug Delivery System Based on Magnesium Aluminate Layered Double Hydroxide

Abstract: This paper reviewed our research progress in respects of th intercalation law of acetylsalicylic acid (ASP) with magnesium aluminate layered double hydroxide (LDH), the drug release mechanism and the tablet preparation effect of LDH-ASP system. We also discussed the propositions about the composite assembly rules, slow-release mechanism, and dosage form processing of the layered double hydroxide drug delivery system. Intercalation way and drug structure should be taken into consideration in assembly LDH-drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There is a variety of techniques used for encapsulating drugs, foods and cosmetics, such as: spray-drying, complex coacervation, atomization and liposomes (Gharsallaoui et al, 2007;Gou et al, 2013). When choosing the material to be used for this process, a number of factors must be taken into consideration, such as: physical and chemical properties of the core, porosity and solubility of the wall, viscosity, mechanical properties, filmforming ability and vitreous transition, compatibility of the core with the wall, and the wall material used must be insoluble and non-reactive with the core (Gouin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is a variety of techniques used for encapsulating drugs, foods and cosmetics, such as: spray-drying, complex coacervation, atomization and liposomes (Gharsallaoui et al, 2007;Gou et al, 2013). When choosing the material to be used for this process, a number of factors must be taken into consideration, such as: physical and chemical properties of the core, porosity and solubility of the wall, viscosity, mechanical properties, filmforming ability and vitreous transition, compatibility of the core with the wall, and the wall material used must be insoluble and non-reactive with the core (Gouin, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…After intraperitoneal injection, the magnetic field was disturbed at different sites. The experimental results showed that the concentration of the drug in the rat where the magnetic field was established was significantly higher than that of the tissue away from the magnetic field (Gou et al., 2013 ). This result validated the in vivo magnetic field targeting of the three-stage supramolecular drug transport model.…”
Section: A Drug Delivery System With Controlled Release and Magnetic mentioning
confidence: 99%
“…Figure 3B showed that the characteristic diffractions of the as-prepared CdHgTe samples were correspond to the (111), ( 220) and (311) crystal face diffraction of the cubic system, with the 2θ and d values of (24.42°, 0.369nm), (40.60°, 0.222nm) and (47.08°, 0.193nm), which demonstrated that the crystalline phase of the as-prepared QDs was similar to the sphalerite type cubic syngony of HgTe. The diffractions appeared in Figure 3D at (003) (11.02°, 0.802nm), (006) (22.15°, 0.401nm), (0012) (33.14°, 0.270nm), (0015) (37.31°, 0.241nm), (110) (57.64°, 0.160nm) and (113) (58.89°, 0.157nm) were used to identify the DMF lattice, based on which the DMF lattice was indexed as the R-hexagonal lattice of magnetic layered compound hydroxide [14,15,17] . The characteristic diffraction peaks of the CdHgTe@DMF samples were almost similar to that of CdHgTe and its standard reference crystalline phase 32-0665, while the characteristic diffractions of DMF [14,15,17] were not obvious except a weak diffraction of (006) (23.55 °, 0.377nm), as shown in Figure 3C, due to the fact that the majority part in the composite was CdHgTe, the percentage of DMF was relatively small (the molar ratio of CdHgTe/DMF was 3: 1).…”
Section: Characterization Of Cdhgte and Cdhgte@dmf Samplesmentioning
confidence: 99%
“…a magnetic layered double hydroxide (MLDH) in form of [Fe II x Fe III 2 (OH) 2(x+2) ](A y-) 2/y •(1~2x)H 2 O to integrate magnetic targeting and slow release functions [14] . Based on MLDH, a supra-molecular drugs delivery system of "dextran-magnetic layered double hydroxide-fluorouracil" (DMF) was synthesized [15][16][17][18] . To achieve visualization for magnetic targeting therapeutic effect of the DMF system, we prepared water-soluble near-infrared CdHgTe QDs as a fluorescent agent to trace DMF particles.…”
Section: Introductionmentioning
confidence: 99%